1981
DOI: 10.1111/j.1471-4159.1981.tb01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptidase Regulation of Gonadotropin‐Releasing Hormone Levels During In Vitro Incubations of the Rat Hypothalamus

Abstract: The fate of gonadotropin-releasing hormone (GnRH) was examined by a GnRH radioimmunoassay during in vitro incubations of the rat medial basal hypothalamus (MBH). There was a progressive disappearance of exogenous GnRH during MBH incubations. The GnRH degradation could be explained by the release of peptidases from the MBH into the incubation medium. The cytoplasmic marker lactic dehydrogenase (LDH) was also released into the incubation medium. The peptide antibiotic bacitracin produced a dose-dependent inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In vitro incubation experiments of hypothalamic tissue have shown their usefulness in studies on LHRH release in adult rats [3,4,14,19,20,22,23]. In the present study we describe in vitro release of LHRH from MBH of developing rats.…”
Section: Discussionmentioning
confidence: 88%
“…In vitro incubation experiments of hypothalamic tissue have shown their usefulness in studies on LHRH release in adult rats [3,4,14,19,20,22,23]. In the present study we describe in vitro release of LHRH from MBH of developing rats.…”
Section: Discussionmentioning
confidence: 88%
“…The demonstration that a synthetic fragment of LHRH is capable of enhancing lordotic posture suggests that peptidase activity may also be important in the modulation of mating behavior. When exogenous LHRH was incubated with hypothalamic tissue, a significant disappearance of the molecule was observed within 30 min [17], After 2 h, 75% of the LHRH had disappeared. En hancement of mating behavior following infusion of LHRH into the VMH has been reported to occur between 60 and 90 min after infusion [1], which is a sufficient amount of time for significant degradation to have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Veratrine depolarizes nerve tissue through an activation of sodium channels sensitive to tetrodotoxin [19,27], and causes a calciumdependent release of numerous neurohor mones [18,20,21], We have found veratrine to release GnRH from the MBH at concen trations which release little LH from hemipituitaries and which increase the sensitivity of the pituitary to GnRH [20], The properties of veratrine permitted its use in brain-pituitary coincubations to determine whether LH and/or FSH releasing factors other than GnRH could be released from brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH levels are constant during hemipituitary incubations with synthetic GnRH, however, we have demonstrated that GnRH immunoreactivity linearly increases during 4-hour MBH incubations in the presence of veratrine [21]. The first 30 min of GnRH release occurs in the absence of a hemipituitary using the coincubation technique em ployed; thus, the mean GnRH concentration the hemipituitary is exposed to should equal 55% of the concentration measured at the end of the coincubation.…”
Section: Correlation O F Lh and Fsh Release With Gnrh Release During mentioning
confidence: 99%
See 1 more Smart Citation